(untitled) (Third Sector Social Economic Review, 2022)
This study includes the findings regarding the validity and reliability of the Turkish adaptation of the scale of unethical pro-organizational behavior, which was developed by Umphress et al. (2010). The scale adaptation study was carried out with data obtained from two different samples (n1= 508, n2= 330). As a result of the analyzes made, it was determined that the scale exhibited a one-dimensional structure in accordance with the factor structuring in the original scale. In addition, the criterion-dependent validity of the scale was carried out by using the organizational identification, machiavellianism (dark triad of personality) and moral distancing scales. As a result of the reliability analysis, 0.901 for the first sample; for the second sample, it was calculated as 0.906. The results obtained showed that the adapted scale is valid and reliable for evaluating the unethical pro-organizational behavior of employees in the field of organizational behavior in Turkey.